Making the Most of Where You Are: Geography, Networks, and Innovation in Organizations - Funk, Russell J. (Academy of Management Journal, 2014)
Drawing on insights from macro- and microlevel research, I develop and test a theory of how the makeup of firms' local environments influences their ability to generate innovations. I propose that although geographic proximity to industry peers can enhance performance, such effects are moderated by intraorganizational network structures. Data on collaborations among inventors and the geographic locations of 454 US companies active in nanotechnology R&D between 1990 and 2004 are used to show that as proximity to industry peers decreases—and knowledge spillovers become less common—inefficient networks are beneficial because they create and sustain diversity internally. For firms with high proximity, more cohesive network structures that facilitate information processing are desirable.